Combined d-SPE-QuECHERS-Cold Bath Extraction and GC/MS for the Determination of 24 Polycyclic Aromatic Hydrocarbons in Stranded Green Sea Turtles, Chelonia Mydas (Linnaeus, 1758). (9th August 2022) - Samara, Fatin; Alam, Isra Arshad; Yaghmour, Fadi
Abstract: Priority pollutants polycyclic aromatic hydrocarbons (PAHs) in muscle and livers of stranded green sea turtles, Chelonia mydas (Linnaeus, 1778) were extracted using a quick, easy, cheap, effective, rugged and safe method followed by Gas chromatography/mass spectrometry (GC/MS). Changes to the nature of the extracting solvents, the reaction conditions and the number of co-extractives in the extraction procedure was established to account for the variability of the tissue samples' matrix effect and condition code of each turtle examined. The analytical performance was assessed taking into consideration the analytical recoveries at different fortification levels, matrix effect and instrumental parameters such as selectivity, linearity, and the limits of detection and quantification. Recoveries between 72 and 162% were obtained for most PAHs in liver and 24-107% in muscle samples. Matrix effects assessments showed medium matrix effect, while LOD was on average 0.04 µg g −1 and LOQ was on average 0.13 µg g −1 . The extraction showed the best recoveries when extracted using acetonitrile at cold temperature conditions of around 4 °C. Validation results through PCA and correlation analyses showed the suitability of this method for simultaneous determination and confirmation of PAHs in both liver and muscle of stranded turtles at different decomposition levels, matrix complexities and specimen sizes.